Seasonal patterns of evapotranspiration, soil moisture, rainfall, and normalized difference vegetation index in a Nama-Karoo ecosystem - Gqaleni, Nosipho Onwabile (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.